PM.89 Severe Headaches in Pregnancy. First Presentation of Arnold Chiari Malformation Type 1. (26th April 2013) - Iftikhar, S; Ghani, R
Abstract : Arnold Chiari malformation is a malformation of the brain which consists of a downward displacement of the cerebellar tonsils through the foramen magnum. Type 1 Arnold Chiari is generally asymptomatic during childhood. It can typically present in women during early adulthood and can be a cause of unexplained headaches and cerebellar symptoms. We present a case of 32 year old primigravida with severe headache and visual loss for the first time in pregnancy. She had a twin pregnancy after successful IVF. She also developed gestational diabetes. Magnetic resonance imaging of the brain showed Arnold Chiari malformation type 1. We describe the management of this case during the antenatal and intrapartum period. She was delivered by emergency caesarean section under general anaesthetic. Her visual loss was thought to be secondary to optic neuropathy with an unknown cause and it remains a clinical dilemma until now. We discuss multidisciplinary team management and careful anaesthetic assessment in such cases.